ANALISIS STRATEGI PENETAPAN HARGA DAN PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN PADA FOODBOX - Astuti Astuti; Muhajirin Muhajirin (Jurnal Bina Bangsa Ekonomika, 2022)
A good pricing and promotion strategy will have an impact in increasing sales volume so that the company's revenue can achieve large profits. This study aims to find out how good the streatgei of pricing and promotion is in increasing sales volume on Foodbox. This type of research is descriptive. The research instrument used is a likert scale questionnaire that has been distributed. The population in this study was all Foodbox customers with a sample of 50 respondents with the sample determination technique used in this study was non-probability sampling using the accidental sampling method. Data collection techniques use observations, questionnaires and literature studies. The data analysis technique uses validity test, reliability test, normality test and t test test one sample. The results showed that the pricing strategy in increasing sales volume at Foodbox was not good, while promotion in increasing sales volume at Foodbox was good because it was more than 75%